Nite owls [compact disc] - McPherson, J. D., 1977- (New West Records, 2024)
JD McPherson has created something unique and amazing with his latest album, his first album release since 2018's critically acclaimed Christmas classic, SOCKS. Over the past five plus years, McPherson has stayed consistently busy writing new songs while at the same time touring with Alison Krauss and Robert Plant. With this album, JD wanted to try something new and different. He wanted to take the inspiration from multiple decades and styles and incorporate them into his own sound. It delivers the signature sounds of vintage garage-rock while also seamlessly bridging the sounds of Bowie and Alan Vega. McPherson takes inspiration from multiple genres of the past and combines them together to evolve a sound that is all his own.